The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/pme.12594
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Use among Chronic Pain Patients Prescribed Opioids: Associations with Pain, Physical and Mental Health, and Health Service Utilization

Abstract: CNCP patients using BZDs daily represent a high-risk group with multiple comorbid mental health conditions and higher rates of emergency health care use. The high prevalence of BZD use is inconsistent with guidelines for the management of CNCP or chronic mental health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
94
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 36 publications
7
94
3
Order By: Relevance
“…It is well‐known that opioid users, especially long‐term high dose opioid users, have increased risks for co‐medication with BZDs or Z‐hypnotics compared with non‐opioid users . Likewise, in our study, high‐dose opioid users were also high‐dose users of sedative.…”
Section: Discussionsupporting
confidence: 62%
“…It is well‐known that opioid users, especially long‐term high dose opioid users, have increased risks for co‐medication with BZDs or Z‐hypnotics compared with non‐opioid users . Likewise, in our study, high‐dose opioid users were also high‐dose users of sedative.…”
Section: Discussionsupporting
confidence: 62%
“…10,11,28,29 and we found that hypnotics and skeletal muscle relaxants were also associated with longer opioid durations and co-prescribing these drugs have also been shown to be associated with opioid use. 6,15,25 Our analyses show that the likelihood of opioid discontinuation is slowly increasing with time (HR=1.02 in 2007 vs HR=1.11 in 2014) which suggests that prescribers may be becoming more aware of the harms of long-term opioid use.…”
Section: Discussionmentioning
confidence: 76%
“…More specifically, the study used data from 16 years of the National Health and Nutritional Examination Survey (NHANES) for years 1999 to 2014 to examine trends in use of prescription opioids as well as long‐term use of opioids. In addition, associations of long‐term use with indicators of elevated risk of adverse effects from opioid treatment were examined, including presence of painful conditions, severe medical conditions, concomitant use of benzodiazepines, and history of heroin and alcohol misuse …”
Section: Introductionmentioning
confidence: 99%